Chemisorption of enrofloxacin on rutile-TiO2 (110) surface: a theoretical investigation - Tri, Nguyen Ngoc; Dai, Ho Quoc; Trung, Nguyen Tien (Vietnam Journal of Science and Technology, 2019)
We investigated the adsorption of enrofloxacin (ENR) antibiotic on rutile-TiO2 (r-TiO2) (110) surface using DFT calculations. Stable configurations of the adsorption of ENR on r-TiO2 (110) were observed. The origin and role of interactions in stablizing the configurations are thoroughly analyzed using NBO and AIM analyses. Obtained results indicate that the adsorption process is characterized as a strong chemisorption with an associated energy of ca. -35.1 kcal.mol-1 for the most stable configuration. Quantum chemical analysis shows that the stability of configurations is mainly determined by >C=O∙∙∙Ti5f electrostatic interaction along with supplement of H∙∙∙Ob hydrogen bond.